PENGUATAN SPIRITUALITAS ISLAM MELALUI BUDAYA PROFETIK - Mohamad Roqib (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article describes prophetic culture which is implemented to Javanese society. There are three important pillars, namely transcendence, liberation, and emancipation. These pillars are understood clearly and elaborated in detail. Those indicators are used as the guidance on implementing a more dignified human life.